The Influence of City Branding on Visit Intention, Mediated By Brand Identity and City Image, and Its Impact on Visit Decisions - Rais Akbar; Zainul Arifin; Edriana Pangestuti (LPPM Universitas PGRI Sumatera Barat, 2023)
This study examines the relationship between city branding and intention to visit by considering the mediating roles of brand identity and city image, as well as their ultimate influence on the decision to see, through a case study of tourists visiting Makassar City, which is branded as the